Pelatihan Media Daring untuk Staf Administrasi: Online Media Training for Administrative Staff - Gita Danu Pranata; Misbahul Anwar; Jefree Fahana (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
In the 21st century, the Industrial Revolution 4.0, the Covid-19 pandemic, accelerated Muhammadiyah's organizational transformation by optimizing media and online methods as organizational needs. The Covid pandemic has been running for more than a year. Still, as human resources responsible for preparing online media, the administrative staff and the secretary of the institutional assembly still often face technical problems that cannot be resolved quickly. The goal to be achieved in this service program is to provide education and training so that the staff and secretary of the institutional assembly can optimize online media and methods and can solve technical problems in emergencies. The implementation method of this program is online training to provide a basic general understanding, followed by offline training to practice zoom webinar media as MC and Online Moderator. The results and implications of this program are that participants can understand and implement the zoom webinar media as MC and Online Moderator in their respective duties. The conclusion is that after this community service program is held; participants can understand and implement the Zoom webinar media as MC and Online Moderator in their respective duties professionally.